2015
DOI: 10.1016/j.jad.2015.02.002
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative investigation into the relationships between social factors and suicidal thoughts and acts experienced by people with a bipolar disorder diagnosis

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. AbstractBackground: The prevalence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
26
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 62 publications
2
26
1
Order By: Relevance
“…In many correctional settings, including the department of corrections that was the source for our data, offenders classified at the maximum level reside in single bed units (i.e., they do not share living quarters), and contact with other offenders is minimal. The association between maximum security and suicide attempts may be related to offenders experiencing a negative environment, increased stress, reinforcement of negative self-worth, and social isolation [28,30,41]. The majority of offenders classified as maximum security were tobacco smokers (64.5%) and a plurality had a diagnosis of depression (38.4), significant risk factors for suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In many correctional settings, including the department of corrections that was the source for our data, offenders classified at the maximum level reside in single bed units (i.e., they do not share living quarters), and contact with other offenders is minimal. The association between maximum security and suicide attempts may be related to offenders experiencing a negative environment, increased stress, reinforcement of negative self-worth, and social isolation [28,30,41]. The majority of offenders classified as maximum security were tobacco smokers (64.5%) and a plurality had a diagnosis of depression (38.4), significant risk factors for suicide attempts.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, depression and bipolar with anxiety disorders are strongly associated with suicidal ideation, attempts, and completion [3,20,21,22,23,24,26,29,30,31]. Individuals with SUD also have greater incidence of suicidal ideation and attempts compared to the population who do not have a problem with substances [32,33].…”
Section: Introductionmentioning
confidence: 99%
“…Second, to minimise problems with recall, the inclusion criteria specified that participants must have had experience of suicidal thoughts or behaviours in the past year 38. For some participants, memories regarding sleep in the more distant past were often more generalised in comparison with recollections of suicidal experiences.…”
Section: Discussionmentioning
confidence: 99%
“…Suicide is a cause of death in which psychological factors are directly involved, as the individual ultimately forms a decisive intention to end their own life [1,2,3]. The suicidal downward spiral starts with ideation, which functions as an indicator of vulnerability and might lead to a suicide attempt or suicide.…”
mentioning
confidence: 99%
“…[41,18] A mental health diagnosis is a strong predictor of suicidal behavior and nine out of 10 people who end their life will have experienced clinically signifi-cant mental health problems. [42,3] One potential risk factor that has received comparatively little attention is the stigma associated with mental health problems and associated experience of discrimination. [43,7] It has been suggested that the acceptance of stigmatizing beliefs about mental illness may influence levels of hopelessness.…”
mentioning
confidence: 99%